La dimension sociale de la mobilité quotidienne, oubliée du développement urbain durable ? - Cécile Féré (VertigO)
Urban policies are in a paradoxical situation : they have to offer access to mobility for everyone ; they have to reduce personal car use. Considering the pluralization of mobility’s actors system, this paper is addressing the issue of how innovative mobility services compared with transport policies have been taken into account socio-spatial inequalities for access to mobility : taking for example the case of Lyon Urban Community, we compare access to work initiatives and Inter-Companies Commuter Plans which aim at improving access to mobility with social dimension of transport policy. Actors outside transport sector have adopted “orphaned issues” (Gauthier and Paulhiac, 2008) of transport policies since the middle of the 1990s and the 2000s, while the transport policies have remained faithful to the ideals of the “right to transport” and let play the “patrimonial transmission” (Scherrer, 1999). Those innovative provisions that are strongly territorialized and targeted have a limited impact on reducing inequalities of access to mobility. They are more and more submitted to sustainable mobility injunction like transport policies for defining both strategies and action plans. Social dimension of mobility seems left out the sustainable urban development facing economical and environmental issues.